Pengaruh Konservatisme Akuntansi, Deferred Tax Expense, Capital Intensity, dan Umur Perusahaan terhadap Tax Avoidance (Studi Empiris Pada Perusahaan Sektor Consumer Non Cyclicals di Bursa Efek Indonesia Tahun 2018 - 2022) - Harefa, Jeni Mardiana Novritasari; Margie, Lyandra Aisyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to test and analyze the effect of Accounting Conservatism, Deferred Tax Expense, Capital Intensity and Company Age on Tax Avoidance. in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This type of research is quantitative research. The analysis method of this study uses multiple linear regression analysis, using E-views 9. Sample selection in this study using the purposive sampling method, namely sample selection based on predetermined criteria, obtained as many as 45 data observations. The results of testing on the study showed that simultaneously Accounting Conservatism, Deferred Tax Expense, Capital Intensity and Company Age had a significant effect on Tax Avoidance. Partially, the age of the company has a significant effect on tax avoidance, while accounting conservatism, deferred tax expense and capital intensity do not have a significant effect on tax avoidance.